THE IMPACT OF LITERATURE IN TEACHING A FOREIGN LANGUAGE – A CASE STUDY ON THE USE OF DRAMA AND ITS PRACTICAL IMPLICATIONS - Anxhela Starja (European Scientific Journal, ESJ, 2015)
The ever-increasing need to communicate and be up to date with the language changing dimension and the continous interactions worldwide impose learners and teachers of foreign languages to consider all proven and meaningful means of language acquisition in order to develop skills and competences. Through the review of literature we can reiterate and properly estimate the traditional role of literary texts in our teaching process but it is through our practical considerations and efforts within the classroom setting, through detailed and conspicious patterns of literature that we can feel its immense power and results on our students. This paper aims at highlighting the impact of drama in our students’s learning process, how it fosters autonomy, eagerness, motivation and creativity. These will be reinforced in a case study organized with the English Study Skills class in the Faculty of Foreign Languages, University of Tirana, Albania.